2006
DOI: 10.1590/s0034-71672006000300006
|View full text |Cite
|
Sign up to set email alerts
|

Aplicando recomendações da Escala de Braden e prevenindo úlceras por pressão: evidências do cuidar em enfermagem

Abstract: Recorte ampliado da Dissertação de Mestrado em Enfermagem da Faculdade de Enfermagem da UERJ. RESUMOQuestiona-se o risco de acometimento de úlcera de pressão (UP) no cliente, e a validade do cuidado de enfermagem aplicando a escala de Braden para verificar as evidências desse cuidado na incidência da UP. Utilizou-se o método de medidas biofisiológicas em clientes de UTI. Encontrou-se 11 clientes com UP, numa incidência de 26,83%. A maioria (57,1%) de úlcera encontra-se no estágio I. Clientes com UP têm escores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
37

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 5 publications
0
7
0
37
Order By: Relevance
“…And most of the studied population has developed PU, and 64% presented two injuries. In regards to detected PU incidence (59.5%) in Brazil, the problem's estimative at chronic care units was diversified, but some identified publications has shown a lower incidence in comparison to what was found during this research, like 5.9%; 39.7%; 26.8% and 11.8%, respectively (25)(26)(27)(28) . Thereby, it is urgent and necessary that preventive care attitudes can be performed; even in order to reverse other morbidities that have probably been caused by these injuries.…”
Section: Discussionmentioning
confidence: 61%
“…And most of the studied population has developed PU, and 64% presented two injuries. In regards to detected PU incidence (59.5%) in Brazil, the problem's estimative at chronic care units was diversified, but some identified publications has shown a lower incidence in comparison to what was found during this research, like 5.9%; 39.7%; 26.8% and 11.8%, respectively (25)(26)(27)(28) . Thereby, it is urgent and necessary that preventive care attitudes can be performed; even in order to reverse other morbidities that have probably been caused by these injuries.…”
Section: Discussionmentioning
confidence: 61%
“…Nos demais estados brasileiros, identificamos apenas um estudo do Rio de Janeiro com incidência de 26,8% em UTI (16) e um na Bahia, que estudou os setores de internação inclusive UTI, em dois hospitais, com incidência de 31,4% e 21,4%, respectivamente (17) . Na análise estatística sobre associação de idade, sexo, cor e tabagismo com presença de UP, nenhum resultado significativo foi encontrado, pois todos apresentaram p > 0,005.…”
Section: Resultsunclassified
“…In a recent literature review, however, the authors found higher incidence rates, from 38% to 124%, in the studies examined (5) . In Brazil, concern regarding the incidence of PU in ICU patients has also been increasing, with studies conducted in Rio de Janeiro and São Paulo, reporting incidences from 26.83% to 62.5% (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%